Mortality Among Dengue Infection Patients in Bandung City 2022 - Salsabila, Diyana; Ningrum, Dina Nur Anggraini; Khasanah, Amelia Fitra; Alwi, Luqman; Andar, Nadiya Arawinda; Palgunadi, Palgunadi (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Dengue infection is caused by the dengue virus. In 2021 in Indonesia, 705 mortalities were due to dengue infection, while in 2022, 1,232 mortalities. The CFR in 2019 was 0.67%, in 2020 it was 0.69%, and in 2021 it was 0.96%. Bandung City is one of the endemic areas. In 2022, found 21 reported mortality, with a CFR of 0.47% in 2020, 0.35% in 2021, and 0.19% in 2022. Risk factors for death due to dengue infection are old age, delay in treatment, platelet count, incidence of DSS, and hematocrit value. This is a quantitative observational study using a nested case-control research design. Uses secondary data from the Bandung City Health Service. The results of this study confirmed association of mortality with age above 40 years (p-value: 0.008, OR: 6.320), high hematocrit value (p-value: 0.005, OR: 11.111), long gap between onset and diagnosis (p-value: 0.025, OR: 13.833), prolonged hospitalization (p-value: <0.001, OR: 8.125), and incidence of DSS (p-value <0.001, OR: 39.500). Low platelet count (p-value: 0.033, OR: 0.263) found to be protective. Age, hematocrit value, gap between onset and diagnosis, length of hospitalization, and incidence of DSS are risk factors for mortality among dengue infection patients.